2017
DOI: 10.2166/wst.2017.331
|View full text |Cite
|
Sign up to set email alerts
|

Continuous transformation of chiral pharmaceuticals in enzymatic membrane bioreactors for advanced wastewater treatment

Abstract: This study demonstrates continuous enantiomeric inversion and further biotransformation of chiral profens including ibuprofen, naproxen and ketoprofen by an enzymatic membrane bioreactor (EMBR) dosed with laccase. The EMBR showed non-enantioselective transformations, with high and consistent transformation of both (R)- and (S)-ibuprofen (93 ± 6%, n = 10), but lower removals of both enantiomers of naproxen (46 ± 16%, n = 10) and ketoprofen (48 ± 17%, n = 10). Enantiomeric analysis revealed a bidirectional but u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…After sampling, 0.1 mL of methanol was added prior to quantitative analysis. As naproxen is known for its resistance to enzymatic biodegradation [20] 0.1 mM of ABTS was added as a mediator agent to the solutions of that pharmaceutical.…”
Section: Biodegradation Of Pharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sampling, 0.1 mL of methanol was added prior to quantitative analysis. As naproxen is known for its resistance to enzymatic biodegradation [20] 0.1 mM of ABTS was added as a mediator agent to the solutions of that pharmaceutical.…”
Section: Biodegradation Of Pharmaceuticalsmentioning
confidence: 99%
“…The presence of the mediator is required to achieve satisfactory rates of reaction, as it is known that naproxen is insufficiently oxidized by the laccase and is resistant to enzymatic degradation [20]. The significant drop in the rates of degradation of both anti-inflammatory drugs at pH 7 is related to the formation of hydroxide ions, which can bind to the T2/T3 copper ions in the laccase structure.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Chiral inversion of S(+)-naproxen to R(-)-naproxen has been observed previously during wastewater treatment (Hashim et al, 2011;Suzuki et al, 2014). Furthermore, Nguyen et al (2017) reported bidirectional inversion of anti-inflammatories (naproxen, ibuprofen and ketoprofen) by an enzymatic membrane bioreactor. The results of the single enantiomer microcosms agree with those of the racemic microcosm whereby an enrichment of S(+)-naproxen was found (Figure 1).…”
Section: Transformation Processes Responsible For Enantiospecific Drug Changesmentioning
confidence: 55%
“…Similarly, fungi such as Verticillium lecanii have been found to preferentially convert R(-)-ibuprofen to S(+)-ibuprofen by an enzymatic process related to mammalian studies (Thomason et al, 1998). However, evidence reporting the inversion of S(+)-ibuprofen to R(-)-ibuprofen by Nocardia bacteria exists (Mitsukura et al, 2002), as well as in lake water microcosms (Buser et al, 1999) and during wastewater treatment (Nguyen et al, 2017). The mechanism of chiral inversion remains poorly understood, particularly in the environment, but it is believed several enzymes play a role (Kato et al, 2003;Kato et al, 2004;Khan et al, 2014).…”
Section: Transformation Processes Responsible For Enantiospecific Drug Changesmentioning
confidence: 99%
“…Batch and flow through microcosm studies using spiked enantiomer concentrations enable a greater understanding of these processes whereby operational variables can be closely controlled. Several studies have reported limited or no enantioselectivity of ibuprofen in batch studies of diluted activated sludge (Escuder-Gilabert et al 2018) or laccase enzyme obtained from a culture of the white rot fungus Pleurotus ostreatus (Nguyen et al 2017). Furthermore, no enantioselectivity was observed in constructed wetlands treating synthetic or real wastewater under predominantly anaerobic conditions at dissolved oxygen concentrations less than 0.5 mg L −1 (Matamoros et al 2009).…”
Section: Spiked Wastewater Microcosms For Fate Evaluationmentioning
confidence: 99%